Pan-Africanism or Pragmatism? Lessons of Taganyika-Zanzibar Union - Shivji,Issa G. (Dar es Salaam Mkuki na Nyonta Publishers, 2008)
This is a lucid study of the background and the major dramas of the Union of Tanganyika and Zanzibar. It studies the personalities and their politics, and includes a gripping account of the Dodoma CCM conference that toppled President Jumbe. It is also a meticulously detailed and illuminating legal analysis of the union constitution, incorporating powerful new material.
Keywords: Pan-Africanism